PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN SERVICE (STUDI PADA SERVICE MOBIL PT. PEKAN PERKASA BERLIAN MOTOR PEKANBARU - Ashifa Tania; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of organization commitment and Work Motivation on Job Satisfaction Of Service Employee PT. Pekan Perkasa Berlian Motor Pekanbaru partially and simultaneously. This study uses questionnaires as a means of collecting data distributed to 41 the employees of service PT. Pekan Perkasa Berlian Motor Pekanbaru. Data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 25.0 by performing validity test, reliability test, simple linear regression analysis, multiple linear analysis, coefficient of determination analysis, and hypothesis test consisting of t test (partial) and F test (simultaneous). This result showed that the result of the first hypothesis testing is service quality to customer satisfaction showed t count (9,686) > t table (2,022), it means Organization Commitment significantly influence Job Satisfaction. The result of second hypothesis testing is Work Motivation to Job satisfaction show t count (7,481) > t table (2,022), it means Work Motivation have significant effect to Job satisfaction. The result of the third hypothesis testing, namely Organization Commitment  and Work Motivation on Job satisfaction show F count (23,327) > F table (3,24), it means Organizational Commitment and Work Motivation have significant effect to Job satisfaction.  Keywords: Organizational Commitment, Work Motivation and Job Satisfaction